Penguatan Soft Skill dan Hard Skill melalui Pelatihan Public Speaking dan Pengkabelan Jaringan Komputer di SMA Negeri 1 Sorong (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
This community service activity aims to strengthen students’ soft skills and hard skills through public speaking and computer network cabling training at SMA Negeri 1 Sorong City. The activity's background is rooted in the state of computer learning, which still focuses on the introduction of software and hardware, while communication skills and computer network practices have not been fully developed. The method for implementing the activity uses an experiential learning approach, comprising the planning, socialization, training, and evaluation stages. Soft skills training is focused on improving public speaking skills through public speaking practice, while hard skills training is carried out through direct practice of computer network cabling using UTP cables and supporting devices. The results of the activity show an increase in students’ communication skills and self-confidence, as well as an increase in students' understanding and technical skills in computer network cabling. This activity provides an applicable learning experience and strengthens the synergy between universities and high schools in developing student